2020
DOI: 10.1186/s12934-020-01307-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimized expression and enhanced production of alkaline protease by genetically modified Bacillus licheniformis 2709

Abstract: Background: Bacillus licheniformis 2709 is extensively applied as a host for the high-level production of heterologous proteins, but Bacillus cells often possess unfavorable wild-type properties, such as production of viscous materials and foam during fermentation, which seriously influenced the application in industrial fermentation. How to develop it from a soil bacterium to a super-secreting cell factory harboring less undomesticated properties always plays vital role in industrial production. Besides, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 49 publications
(62 reference statements)
0
20
1
Order By: Relevance
“…It is considered as an efficient expression system with several advantages, such as rapid growth rate to result in short fermentation cycles, distinguished ability to secrete significant amounts of proteins into the extracellular medium, easy cultivation and genetic manipulation [ 1 ]. A variety of proteases have been successfully expressed in B. subtilis , including an alkaline protease (AprE) from Bacillus licheniformis 2709 [ 11 , 12 ], a serine protease (AprB) from Bacillus sp. strain B001 [ 13 ], a neutral protease (NprT) from G. stearothermophilus [ 14 ], and alkaline serine proteases from Bacillus clausii (aprE) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as an efficient expression system with several advantages, such as rapid growth rate to result in short fermentation cycles, distinguished ability to secrete significant amounts of proteins into the extracellular medium, easy cultivation and genetic manipulation [ 1 ]. A variety of proteases have been successfully expressed in B. subtilis , including an alkaline protease (AprE) from Bacillus licheniformis 2709 [ 11 , 12 ], a serine protease (AprB) from Bacillus sp. strain B001 [ 13 ], a neutral protease (NprT) from G. stearothermophilus [ 14 ], and alkaline serine proteases from Bacillus clausii (aprE) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on genomics, bioengineering methods were applied to enhance the α-amylase in the aprA-deficient strain of Bacillus licheniformis for increasing SBM utilization rate ( 34 ). The key enzymes proteases involved in FSBM can be modified to enhance the expression according to genome association analysis ( 35 , 36 ). Genome research will further improve the quality of SBM fermented by N-11 strain, which is the further research direction.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [112] found that introducing specific mutations from one hyper-cellulolytic strain into another is a feasible strategy to improve cellulase production. Zhou et al [113] were able to improve enzyme activity by 62.19% using modified hosts when compared with wild-type alkaline protease-producing strain B. licheniformis. Presently, the use of lignocellulosic materials requires more technological developments to make it more feasible, cost-effective, and compatible in the real industrial sense.…”
Section: Challenges Impeding the Use Of Lignocellulolytic Enzymesmentioning
confidence: 99%